1995
DOI: 10.1677/jme.0.0140337
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of antisense human chorionic gonadotrophin-α subunit cDNA expression in human choriocarcinoma JAR cells

Abstract: The biosynthesis of human chorionic gonadotrophin (hCG) is a hallmark endocrine function of human choriocarcinoma cells. The present study investigated the consequences of greatly diminishing this synthesis in JAR cells by stably transfecting them with pRSV-antisense hCG-alpha cDNA expression vector. The vector directs the synthesis of antisense hCG-alpha subunit mRNA which would then bind to sense hCG-alpha subunit mRNA, thus blocking its translation and consequently dimer hCG protein synthesis. The transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…There is a possibility that high hCG ␤-subunit concentrations could result in the formation of homodimers that could potentially mimic heterodimers due to conformation similarity. A reduction in hCG synthesis was found to have no effect on cell proliferation in human choriocarcinoma JAr cells (24). Furthermore, Lei et al (36) demonstrated that the tumorigenic effects of hCG did not include an increase in cell proliferation, but, rather, decreased apoptosis and increased the ability of cell invasion of JAr cells in nude mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a possibility that high hCG ␤-subunit concentrations could result in the formation of homodimers that could potentially mimic heterodimers due to conformation similarity. A reduction in hCG synthesis was found to have no effect on cell proliferation in human choriocarcinoma JAr cells (24). Furthermore, Lei et al (36) demonstrated that the tumorigenic effects of hCG did not include an increase in cell proliferation, but, rather, decreased apoptosis and increased the ability of cell invasion of JAr cells in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of recombinant plasmid expression vectors that direct synthesis of antisense mRNA has been performed to inhibit the translation of sense mRNA in different cells in vitro (22)(23)(24)(25)(26)(27). Using this procedure, either reduction of endogenous protein synthesis (22)(23)(24)(25) or cellular growth inhibition was achieved in certain cells (26,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If this were to be the case, inhibition of hCG biosynthesis will have consequences to choriocarcinoma cells. To test this possibility, hCG synthesis was inhibited by stable transfection with antisense of gonadotropin-α subunit cDNA [16]. The antisense α-subunit transcripts made will dimerize with protein coding sense α-subunit transcripts and the dimers formed will then be rapidly degraded by nucleases.…”
Section: Why Do Gtns Overproduce Hcgmentioning
confidence: 99%
“…ASODN may provide a novel approach to therapy of gastric cancer. The antisense technology was used to study several protein actions: the alpha subunit of human chorionic gonadotrophin in choriocarcinoma cells (Cao et al, 1995); the regulating protein E2F-1, in S cellular cycle phase, and its action on genes linked to proliferation (Sala et al, 1994); nerve growth factor (NGF) in skin of transgenic mice, and its relationship with response to mechanical stimuli (Davis et al, 1993). Lately, the antisense strategy is "classically" used to analyze gene expression and intron splicing.…”
Section: Antisense Approachmentioning
confidence: 99%